Photonic Crystals: Magnetoresponsive Discoidal Photonic Crystals Toward Active Color Pigments (Adv. Mater. 33/2014). (September 2014) - Lee, Hye Soo; Kim, Ju Hyeon; Lee, Joon‐Seok; Sim, Jae Young; Seo, Jung Yoon; Oh, You‐Kwan; Yang, Seung‐Man; Kim, Shin‐Hyun
<x xml:space="preserve">Abstract</x> Morpho butterflys show beautiful colors that arise from periodic nanostructures. Inspired by the butterfly, colloidal photonic crystals are designed to have a form of microdisks, which are then further rendered to be magnetoresponsive. On page 5801, S.‐H. Kim and co‐workers demonstrate that magnetic‐field‐controlled flipping of the photonic microdisks enables the switching of structural colors, thereby providing a photonic microdisk display. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>